Boron Trifluoride Etherate-Controlled Reactions of Methyl Enol Ethers: Selective Synthesis of Dihydrofuro[3,2-c]chromenone and Furo[3,2-c]chromenone Derivatives - Ahmad, Sarwat Asma Ziya; Khan, Faiz Ahmed (Synlett, 2022)
A facile one-step synthetic approach to dihydrofuro-[3,2-c]chromenones and furo[3,2-c]chromenones by the reaction of methyl enol ethers with 4-hydroxycoumarins under metal-free conditions is presented. Dihydrofuro[3,2-c]chromenones and furo[3,2-c]-chromenones were selectively obtained by controlling the stoichiometry of boron trifluoride diethyl etherate. An unexpected aryl-group migration followed by aromatization of the furan moiety, leading to a variety of furo[3,2-c]chromenone derivatives in good yields, is reported.
Keywords: methyl enol ethers; furochromenones; Lewis acids; aryl-group migration; tandem reaction; hydroxycoumarin